Peningkatan Perilaku Perawatan Kaki Melalui Edukasi Booklet Smart untuk Pencegahan Diabetic Food Ulcer pada Pasien Diabetes Melitus Tipe 2 - Laila Revalina Madu; Ita Sulistiani Basir; Sitti Fatimah M. Arsad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the effectiveness of the SMART Booklet educational media on foot care behavior in type 2 diabetes mellitus patients at the Limboto Community Health Center. The method used was a pre-experimental design with a one-group pre-test post-test design. The results showed an increase in foot care behavior after the intervention with a p-value of 0.000 (p < 0.05), indicating a significant difference before and after education. In conclusion, education using the SMART Booklet effectively improved foot care behavior in type 2 diabetes mellitus patients. Keywords: SMART Booklet, Diabetic Foot Ulcer, Foot Care Behavior